Ajaran Ekstrem Gereja Masehi Advent Hari Ketujuh dan Ancaman bagi Eksistensi GMIM - Suoth, Novita (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2020)
The rise of various denominations around the world has an impact on the land of Minahasa, where most of the congregations are part of the ministry of the Evangelical Christian Church in Minahasa. There are various strategies employed by various denominations to influence the thinking of church members. GMIM congregation members have not escaped other denominational strategies of